2003
DOI: 10.1200/jco.2003.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for Teratoma With Malignant Transformation

Abstract: Chemotherapy for MT limited to a single cell type may result in major responses and long-term survival in selected patients. Local therapy after chemotherapy is an important component of treatment to achieve maximum response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
163
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(169 citation statements)
references
References 13 publications
4
163
0
2
Order By: Relevance
“…Therefore, the presence of a metastatic STM implies a poor prognosis (2, 3). Nevertheless, Donadio et al (6) showed that systemic chemotherapy may be effective for teratomas with STM limited to a single-cell type. It is recommended that the choice of chemotherapy regimens in such cases should be dictated by the transformed histology rather than the GCT (2, 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the presence of a metastatic STM implies a poor prognosis (2, 3). Nevertheless, Donadio et al (6) showed that systemic chemotherapy may be effective for teratomas with STM limited to a single-cell type. It is recommended that the choice of chemotherapy regimens in such cases should be dictated by the transformed histology rather than the GCT (2, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Unresectable or metastatic settings will generally require multimodal therapy including both chemotherapy and locoregional approaches (6). However, while GCT is sensitive to platinum-based chemotherapy, STM arising from GCT has been traditionally thought to be unresponsive to platinum-based chemotherapy (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Donadio et al reported a response to chemotherapy tailored for malignant transformation histology in three of 10 metastatic cases. 5 More recently, Necchi et al have shown a possible efficacy of TGCT-oriented therapy that combined timely surgery for TGCT with malignant transformation components. 6 However, the application of adjuvant chemotherapy for stage I non-seminomatous TGCT with components Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation is a rare complication of mature cystic teratomas (19). Carcinoid tumors are rare and have been presented as case reports previously (20,21).…”
Section: Discussionmentioning
confidence: 99%